Twenty and ten - Bishop, Claire Huchet; Du Bois, William Pene 1916-. (New York Viking Press, 1952)
Twenty school children hide ten Jewish children from the Nazis during the occupation of France during World War II.
Keywords: World War, 1939-1945 -- Jews -- France -- Fiction; Jews -- France -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction